Economic Performance of Primed Seeds of Some Cultivars of Okra (Abelmoschus esculentus (L.) Moench) (Indian Journal of Extension Education, 2017)
The effect of seed priming on green pod and seed yield and economics of okra cultivation was evaluated for farmers practicability. Four seed priming methods viz. hydropriming, osmopriming, halopriming and solid matrix (SM) priming with different concentrations and durations were employed to 3 cultivars of okra namely A-4, Phule Utkarsha and VRO-6. Among 18 priming treatments of different priming durations along with control, 6 promising treatments in each cultivar resulting in higher vigour index were further selected for field evaluation of green pod and seed yield. All the field operations were kept constant for all treatments and hence variation in cost was only due to the cost of priming agents. Comparison of various treatments revealed that hydropriming for 18h in cv. A-4, halopriming with 1 per cent CaCl2 for 6h in VRO-6 and solid matrix priming for 48h in cv. Phule Utkarsha, were found to be the most beneficial economically for green pod and seed production with maximum benefit cost ratio (BCR) compared with rest of the treatments.